MOST PREFERRED MANUAL THERAPY TECHNIQUE AMONG PHYSIOTHERAPIST FOR TREATING FROZEN SHOULDER - ANWAR ALI GAYASI,; AARTI SAREEN,; TUSHAR J.PALEKAR, (International Journal of Pharma and Bio Sciences, 2014)
All the manual therapy techniques have their pool of research suggesting as effective in treating frozen shoulder. But, it is seen that not all of them are executed while making the rehabilitation protocol for frozen shoulder. So, this survey was conducted in which 120 questionnaires were distributed among physiotherapists of Pune fulfilling the inclusion criterion to know their preferred manual therapy technique for treating frozen shoulder. 100 physiotherapists responded, their responses were documented and calculated. It was found that the most preferred manual therapy technique is Maitland and Mulligan whereas the least preferred in Mckenzie and Cyriax. Their reasons for preference are better clinical results and sufficient evidence for frozen shoulder.